IMPLEMENTATION OF INFORMATION SYSTEM AND COMPLAINT POLICY IN PINRANG DISTRICT - Maulana, Zhulfadli; Guntur, Muhammad; Niswati, Risma (Jurnal Aktor, 2025)
This study aims to determine how the implementation of the information service and complaint system policy in Pinrang Regency. This type of research is qualitative with data collection techniques carried out by observation, interviews, and documentation. The data analysis techniques used consist of data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of the information service and complaint system policy in Pinrang Regency has not been running well according to the policy theory variables by George Edward III with four variables, namely: Communication, resources, disposition, and bureaucratic structure. It is said that it has not run well because there are two policy variables that are not running well, namely the Communication and Resources variables, so that they affect the implementation of the information service and complaint system policy in Pinrang Regency which is not running well. The recommendation from this researcher, then there is a suggestion, namely to improve communication to the community such as even socialization so that people in Pinrang Regency can know what Pindu is. And so with resources, especially financial resources, there is a sufficient budget so that they can carry out socialization to the community or with promotion methods on social media so that people gradually know about the Pindu program.